Method for reforming inferior petroleum coke carbonaceous structure
By mixing the inferior petroleum coke with oxidizing gas and contacting it with compound modifiers, the carbonaceous structure of petroleum coke is solved, and the problem of failure to effectively control the carbonaceous structure of petroleum coke in the prior art is significantly improved.
Patent Information
- Application Number
- CN202311198935.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
The existing reforming of the carbonaceous structure of petroleum coke is mainly focused on desulfurization, and it fails to effectively control the non-ideal carbonaceous structure of petroleum coke, affecting its lithium battery negative electrode performance.
By mixing the inferior petroleum coke with an oxidizing gas (such as nitrogen oxide), then contacting the compound modifier under an inert atmosphere, washing and drying, the carbonaceous structure of the petroleum coke is modified.
Under the premise of slow desulfurization, the carbonaceous structure of petroleum coke is significantly modified and the performance of its lithium battery negative electrode is improved, including improving specific capacity and improving Sd1/Sg indicators.
Smart Images

Figure CN119637838A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon material preparation, and in particular relates to a method for modifying inferior petroleum coke. Background Art
[0002] Petroleum coke is made of vacuum residue oil as the main raw material. It is obtained by the cracking and carbonization of petroleum-derived raw materials such as catalytic cracking oil slurry, ethylene tar, refinery waste oil and scum in the process of delayed coking or fluidized coking in the overall material balance of the refinery. Petroleum coke has a dense intrinsic structure, with carbon as the main element, accounting for ≥85%, hydrogen accounting for about 10%, and other heteroatoms such as nitrogen, sulfur, iron, zinc, cadmium, etc. Petroleum coke can be divided into three categories based on its appearance and properties: sponge coke, which is commonly used as fuel, reducing agent, negative electrode material and prebaked anode; pellet coke for fuel; and needle coke for the production of graphite electrodes and lithium battery negative electrode raw materials. Among them, lithium-ion negative electrode materials are an emerging high-value-added utilization of petroleum coke in recent years. In 2022, the consumption of lithium-ion negative electrode materials will be about 1 million tons. Due to the influence of graphitization process and carbonaceous structure of petroleum coke, lithium battery negative electrode materials require the sulfur content in petroleum coke to be less than 1.5%.
[0003] Petroleum coke, especially ordinary petroleum coke, as a raw material for lithium battery negative electrodes is currently the focus of attention of refineries, major negative electrode and battery cell companies. Ordinary petroleum coke is mainly based on a mosaic structure, and its graphitization tendency is lower than that of needle coke. Therefore, ordinary petroleum coke as a lithium battery negative electrode material has a lower gram capacity, first coulomb efficiency and compaction density than needle coke, making it more suitable for energy storage and markets with demand for charging and discharging rates. However, as a lithium battery negative electrode material, ordinary petroleum coke first has relatively strict requirements on its sulfur content, which is generally required to be less than 1.5%. Secondly, ordinary petroleum coke is required to have a better carbon structure, making it more suitable for lithium battery negative electrode applications.
[0004] The existing work on the carbon structure reforming of petroleum coke is mainly focused on the desulfurization of petroleum coke, because some types of sulfides will hinder the rearrangement of the carbon structure of petroleum coke. However, in addition to sulfides, some non-ideal carbon structures within the petroleum coke itself also have a great impact on the subsequent high value-added applications of petroleum coke. Therefore, in addition to desulfurization, the carbon structure of petroleum coke should also be effectively controlled.
[0005] CN115490227A discloses a method for desulfurization and modification of medium-high sulfur petroleum coke. In this method, medium-high sulfur petroleum coke and a composite treatment agent are mixed, calcined in the presence of ammonia and / or water vapor, desulfurized and modified, and treated materials are obtained. In this method, the harmful sulfur of medium-high sulfur petroleum coke is improved under the joint control of the composite treatment agent and the calcination atmosphere and temperature, so as to improve the electrochemical performance of the graphite negative electrode prepared subsequently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for reforming the carbonaceous structure of inferior petroleum coke. The method of the present invention can adjust the carbonaceous structure of petroleum coke to a greater extent under the premise of slow desulfurization, thereby greatly improving the performance of the lithium battery negative electrode of petroleum coke.
[0007] The present invention provides a method for reforming the carbonaceous structure of inferior petroleum coke, comprising:
[0008] (1) mixing low-quality petroleum coke raw materials with a gaseous oxidant for reaction, and washing and drying the reaction product to obtain a dried product;
[0009] (2) The dried product obtained in step (1) is contacted with a composite modifier to react under an inert atmosphere, and then washed and dried to obtain modified petroleum coke.
[0010] Furthermore, in step (1), the particle size of the petroleum coke is 1-200 mesh, preferably 5-20 mesh. The inferior petroleum coke is high-sulfur petroleum coke, and further, the sulfur content of the petroleum coke is 0.3% to 15%. 1 / Sg is 2.0 or less, preferably 1.8 or less, Sd 3 / Sg is 1.0 or more.
[0011] Furthermore, in step (1), the gaseous oxidant is a nitrogen oxide selected from NO, NO 2 、N 2 O 3 and N 2 O 4 One or more of, preferably N 2 O 4 The gaseous oxidant may contain a carrier gas, which may be one or more of nitrogen and inert gas, preferably nitrogen. The volume content of nitrogen oxides in the gaseous oxidant is 50%-100%.
[0012] Furthermore, in step (1), the low-quality petroleum coke raw material and the gaseous oxidant are mixed and reacted in a fixed bed reactor.
[0013] Furthermore, in step (1), the conditions for the mixed reaction of the inferior petroleum coke and the gaseous oxidant are: temperature of 20-120°C, preferably 30-70°C; pressure of 1-5atm, preferably 1-2atm; volume space velocity of the gaseous oxidant of 50-2000h -1 , preferably 150-1000h -1 , the reaction time is 0.5-12h, preferably 6-10h.
[0014] Furthermore, in step (1), the washing can be performed with water until the mixture becomes neutral. The drying temperature is 60-150° C., preferably 80-120° C., and the drying time is 2-8 hours, preferably 4-6 hours.
[0015] Furthermore, in step (2), the composite modifier comprises alkali, sodium salt and transition metal salt, wherein the mass ratio of alkali: sodium salt: transition metal salt is (0.1-0.5):(8-9):(0.5-1.9), preferably (0.3-0.5):9:(0.5-0.7).
[0016] Furthermore, in step (2), in the composite modifier, the alkali is one or both of potassium hydroxide and sodium hydroxide. The sodium salt is one or both of sodium carbonate and sodium acetate. In the transition metal salt, the transition metal is selected from one or more of iron, cobalt, nickel and manganese, and the salt can be at least one of nitrate, carbonate and chloride.
[0017] Furthermore, in step (2), the mass ratio of the compounded modifier to the dried product obtained in step (1) is 0.1-1:1, preferably 0.3-0.6:1.
[0018] Furthermore, in step (2), the inert atmosphere can be one or more of nitrogen and an inert gas, preferably nitrogen.
[0019] Furthermore, in step (2), the reaction temperature of the composite modifier and petroleum coke is 500-1200°C, preferably 700-900°C.
[0020] Furthermore, in step (2), the reaction time of the composite modifier and petroleum coke is 0.1-6.0 h, preferably 0.3-2.0 h.
[0021] Furthermore, in step (2), the washing can be performed with water until the mixture becomes neutral. The drying temperature is 60-150° C., preferably 80-120° C., and the drying time is 2-8 hours, preferably 4-6 hours.
[0022] Furthermore, compared with the petroleum coke raw material, the specific capacity of the modified petroleum coke is increased by 25% to 70%, preferably by 45% to 70%, for example but not limited to 45%, 55%, 60%, 65%, 70%, etc. The specific capacity of the inferior petroleum coke raw material is less than 290 mAh / g, generally 200 to 240 mAh / g.
[0023] Furthermore, compared with the petroleum coke raw material, the Sd 1 The improvement rate of / Sg is 10% to 60%, preferably 25% to 40%.
[0024] The present invention also provides modified petroleum coke prepared by the method.
[0025] Furthermore, the Sd of modified petroleum coke 1 / Sg is greater than 2.0, Sd 3 / Sg is less than 0.8.
[0026] Compared with the prior art, the method of the present invention has the following advantages:
[0027] 1. In the method of the present invention, inferior petroleum coke is used as raw material, and an oxidizing gas, especially nitrogen oxide, is used to treat the petroleum coke, so that the spacing between the petroleum coke graphite sheets is significantly increased, and then the petroleum coke is treated with a specific compound modifier, which can carry out mass transfer and diffusion along the petroleum coke graphite sheets, thereby realizing the carbon structure reforming of large-particle petroleum coke. Under relatively mild conditions, the performance of the petroleum coke lithium battery negative electrode can be significantly improved.
[0028] 2. The method of the present invention can keep the main structure of petroleum coke intact to the greatest extent, and regulate the carbon structure in petroleum coke in a targeted manner, which is beneficial to improving the performance of petroleum coke lithium battery negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the Raman spectrum of petroleum coke A used in Example 1;
[0030] Figure 2 This is the Raman spectrum of the modified petroleum coke in Example 1;
[0031] Figure 3 This is the Raman spectrum of the modified petroleum coke in Comparative Example 1. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention.
[0033] In the present invention, Raman spectroscopy is used to characterize the carbonaceous structure of petroleum coke. Raman spectroscopy is performed on a HR800 confocal laser Raman spectrometer of HORIBA JobinYvon, France, with a laser wavelength of 532nm, a power of 10mW, and a spectral resolution of 0.65cm -1 , grating 1 800g / mm, Raman shift range 0~2 000cm -1 Among them, d 1 The peak is at 1350cm -1 Nearby, 2 The peak is at 1620cm -1 Nearby, 3 The peak is at 1500cm -1Nearby, 4 The peak is at 1200cm -1 Nearby, the peak of g is at 1580cm -1 Nearby, Sd 1 / Sg、Sd 2 / Sg、Sd 3 / Sg、Sd 4 / Sg represent the peak area ratio of the two peaks. Among them, the g peak represents the ordered graphite structure in petroleum coke, and the d 1 The peak represents the disordered graphite structure in petroleum coke; d 2 The peak is the graphite structure of the mixed ordered and disordered structures in petroleum coke, d 3 The peak represents the amorphous carbon structure in petroleum coke; d 4 The peaks represent the carbonaceous structures in petroleum coke that tend to be polyene-like.
[0034] In the present invention, the petroleum coke before and after modification is air flow crushed to D 50 The thickness of the graphite is 10 to 20 μm. After graphitization, the lithium battery negative electrode performance test, i.e., specific capacity, is carried out according to the GB / T24533-2019 standard for graphite negative electrode materials for lithium-ion batteries.
[0035] The properties of the inferior petroleum coke used in the examples and comparative examples of the present invention are shown in Table 1.
[0036] Table 1 Properties of different petroleum coke raw materials
[0037]
[0038] Example 1
[0039] 50 g of inferior petroleum coke A with a particle size of 5 mesh was loaded into a fixed bed reactor. The reaction temperature was 70°C, the reactor pressure was 2 atm, and the concentration of N 2 O 4 , volume space velocity is 1000h -1 The oxidation treatment time is 8 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0040] The composition of the composite modifier used is sodium hydroxide: sodium carbonate: nickel carbonate, wherein the mass ratio of sodium hydroxide: sodium carbonate: nickel carbonate is 0.5:9:0.5, and the mass ratio of the composite modifier to petroleum coke is 0.5:1. Under nitrogen atmosphere, the reaction temperature is 900°C, and the reaction time is 0.3h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as P-1.
[0041] Example 2
[0042] 50 g of low-quality petroleum coke A with a particle size of 20 mesh was loaded into a fixed bed reactor. The reaction temperature was 70°C, the reactor pressure was 1 atm, and the concentration of N 2 O 4 , volume space velocity is 500h -1 The oxidation treatment time is 10 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0043] The composition of the composite modifier used is potassium hydroxide: sodium acetate: ferric nitrate, wherein the mass ratio of potassium hydroxide: sodium acetate: ferric nitrate is 0.3:9:0.7, and the mass ratio of the composite modifier to petroleum coke is 0.3:1. Under nitrogen atmosphere, the reaction temperature is 700°C and the reaction time is 1h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as P-2.
[0044] Example 3
[0045] 50 g of inferior petroleum coke A with a particle size of 5 mesh was loaded into a fixed bed reactor. The reaction temperature was 70°C, the reactor pressure was 2 atm, and the concentration of N 2 O 4 , volume space velocity is 1000h -1 The oxidation treatment time is 8 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0046] The composition of the composite modifier used is sodium hydroxide: sodium carbonate: cobalt nitrate, wherein the mass ratio of sodium hydroxide: sodium carbonate: cobalt nitrate is 0.4:9:0.6, and the mass ratio of the composite modifier to petroleum coke is 0.6:1. Under nitrogen atmosphere, the reaction temperature is 800°C and the reaction time is 2h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as P-3.
[0047] Example 4
[0048] 50 g of inferior petroleum coke B with a particle size of 5 mesh was loaded into a fixed bed reactor. The reaction temperature was 70°C, the reactor pressure was 2 atm, and the concentration of N 2 O 4 , volume space velocity is 800h -1 The oxidation treatment time is 8 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0049] The composition of the composite modifier used is sodium hydroxide: sodium carbonate: nickel carbonate, wherein the mass ratio of sodium hydroxide: sodium carbonate: nickel carbonate is 0.5:9:0.5, and the mass ratio of the composite modifier to petroleum coke is 0.5:1. Under nitrogen atmosphere, the reaction temperature is 900°C, and the reaction time is 0.3h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as P-4.
[0050] Example 5
[0051] 50 g of inferior petroleum coke B with a particle size of 5 mesh was loaded into a fixed bed reactor. The reaction temperature was 90°C, the reactor pressure was 5 atm, and the concentration of N 2 O 4 , volume space velocity is 300h -1 The oxidation treatment time is 10 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0052] The composition of the composite modifier used is potassium hydroxide: sodium carbonate: iron carbonate, wherein the mass ratio of sodium hydroxide: sodium carbonate: iron carbonate is 0.5:9:0.5, and the mass ratio of the composite modifier to petroleum coke is 0.4:1. Under nitrogen atmosphere, the reaction temperature is 700°C and the reaction time is 2h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as P-5.
[0053] Comparative Example 1
[0054] 50 g of inferior petroleum coke A with a particle size of 5 mesh was loaded into a fixed bed reactor. The reaction temperature was 70°C, the reactor pressure was 2 atm, and the concentration of N 2 O 4 , volume space velocity is 1000h -1 The oxidation treatment time is 8 hours. The oxidized product is then washed with water until neutral and dried at 120°C for 6 hours.
[0055] The composition of the composite modifier used is magnesium hydroxide: sodium carbonate: calcium carbonate, wherein the mass ratio of magnesium hydroxide: sodium carbonate: calcium carbonate is 0.5:9:0.5, and the mass ratio of the composite modifier to petroleum coke is 0.5:1. Under a nitrogen atmosphere, the reaction temperature is 900°C and the reaction time is 0.3h. The reaction product is washed with distilled water until it is neutral, and dried at 120°C for 6h to obtain a product marked as D-1.
[0056] Comparative Example 2
[0057] 50g of inferior petroleum coke A with a particle size of 20 mesh was treated with a compound modifier composed of potassium hydroxide: sodium acetate: ferric nitrate, wherein the mass ratio of potassium hydroxide: sodium acetate: ferric nitrate was 0.3:9:0.7, and the mass ratio of compound modifier to petroleum coke was 0.3:1. The reaction temperature was 700°C and the reaction time was 1h under a nitrogen atmosphere. The reaction product was washed with distilled water until it was neutral, and dried at 120°C for 6h to obtain a product marked as D-2.
[0058] Table 2 Properties of modified petroleum coke in various cases
[0059]
[0060] The embodiments of the present invention are only detailed descriptions of the technical solutions of the present invention, but the present invention is not limited to the above embodiments, that is, the present invention can be implemented without relying on the steps described in the above embodiments. In summary, any improvements made to the present invention by those skilled in the art, as long as they do not deviate from the content of the technical solutions of the present invention, any simple modifications, equivalent changes and modifications made to the above embodiments according to the technical essence of the present invention, shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for reforming the carbonaceous structure of inferior petroleum coke, comprising: (1) mixing low-quality petroleum coke raw material with a gaseous oxidant for reaction, washing and drying the reaction product to obtain a dried product; (2) The dried product obtained in step (1) is contacted with a composite modifier to react under an inert atmosphere, and then washed and dried to obtain modified petroleum coke.
2. The method according to claim 1, characterized in that In step (1), the particle size of the inferior petroleum coke raw material is 1-200 mesh, preferably 5-20 mesh.
3. The method according to claim 1, characterized in that The inferior petroleum coke raw material is high-sulfur petroleum coke. Furthermore, the sulfur content of the petroleum coke is 3% to 15%.
4. The method according to claim 1, characterized in that In step (1), the gaseous oxidant is nitrogen oxide, selected from one or more of NO, NO2, N2O3 and N2O4, preferably N2O4; the volume content of nitrogen oxide in the gaseous oxidant is 50%-100%.
5. The method according to claim 1, characterized in that: In step (1), the low-quality petroleum coke raw material and the gaseous oxidant are mixed and reacted in a fixed bed reactor; preferably, in step (1), the conditions for the mixed reaction of the low-quality petroleum coke and the gaseous oxidant are: temperature of 20-120°C, preferably 30-70°C; pressure of 1-5atm, preferably 1-2atm, and the volume space velocity of the gaseous oxidant is 50-2000h / min. -1 , preferably 150-1000h -1 , the reaction time is 0.5-12h, preferably 6-10h.
6. The method according to claim 1, characterized in that In step (1), the drying temperature is 60-150°C, preferably 80-120°C, and the drying time is 2-8h, preferably 4-6h; and / or, in step (2), the drying temperature is 60-150°C, preferably 80-120°C, and the drying time is 2-8h, preferably 4-6h.
7. The method according to claim 1, characterized in that In step (2), the composite modifier includes alkali, sodium salt and transition metal salt, wherein the mass ratio of alkali: sodium salt: transition metal salt is (0.1-0.5): (8-9): (0.5-1.9), preferably (0.3-0.5): 9: (0.5-0.7).
8. The method according to claim 1, characterized in that In step (2), in the composite modifier, the alkali is one or both of potassium hydroxide and sodium hydroxide; the sodium salt is one or both of sodium carbonate and sodium acetate; in the transition metal salt, the transition metal is selected from one or more of iron, cobalt, nickel and manganese, and the transition metal salt is at least one of nitrate, carbonate and chloride.
9. The method according to claim 1, characterized in that: In step (2), the mass ratio of the compounded modifier to the dried product obtained in step (1) is 0.1-1:1, preferably 0.3-0.6:
1.
10. The method according to claim 1, characterized in that In step (2), the reaction temperature of the compound modifier and petroleum coke is 500-1200° C., preferably 700-900° C.; and / or the reaction time of the compound modifier and petroleum coke is 0.1-6.0 h, preferably 0.3-2.0 h.
11. The method according to claim 1, characterized in that: Compared with the petroleum coke raw material, the specific capacity of the modified petroleum coke is increased by 25% to 70%, preferably by 45% to 70%; and / or, compared with the petroleum coke raw material, the Sd1 / Sg of the modified petroleum coke is increased by 10% to 60%, preferably by 25% to 40%.
12. A modified petroleum coke, characterized in that: Prepared by the method according to any one of claims 1 to 11.
13. The petroleum coke according to claim 12, characterized in that In the modified petroleum coke, Sd1 / Sg is greater than 2.0, and Sd3 / Sg is less than 0.8.
Citation Information
Patent Citations
Method for removing sulfur in petroleum coke and desulfurizer thereof
CN101804977A
Petroleum coke desulfurization method
CN114763263A
Method for modifying high-sulfur coke, method for preparing fast-charging graphite negative electrode material by using high-sulfur coke and application of fast-charging graphite negative electrode material
CN115520860A
Process for calcining and desulfurizing petroleum coke
US4291008A